Active Sports Tourism in Slovenia: Preliminary Research - Damjan Pintar (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Researches from last years in the Alpine space and countries that develop active tourism, shows that tourist, that are interested into active holidays targeting sport oriented or relaxing holidays with elements of sports, are better consumers, higher on the social scale and live in bigger cities. At the same time this consumers spend their holidays several times a year, on a shorter base. Sport is also starting to be one of the main decision-making factors for majority of tourist in this region. This is proved by constant increase of Active sport holidays or Sport related holidays in development of successful tourist destinations in Europe. Goal of this work is to present preliminary research of potentials for active holidays in part of Slovenian mountain region. The research is made in the sample of tourists that are based in hotels and apartments of Slovenian tourist destination Kranjska Gora in the facilities of Hit Alpinea (HA) company. The habits, plans, consumption and type of accommodation related to active holidays were examined.
Keywords: L83; 330; tourist destination; active sports tourism; active lifestyle; Slovenia; HIT Alpinea